ROLE OF PANCHA TIKTA GHRITA GUGGULU ON MAJJA KSHAYA W.S.R. ERYTHROPOIESIS - Dr Ritesh; Kumar, Dr Sandeep (Innovative Research Thoughts, 2017)
Majja Dhatu is the body component similar to bone marrow, the soft organic material that fills the cavities of the bones. Bone marrow is composed of hematopoitic cells, marrow adipose tissue and supportive stromal cells. Bone marrow is primary site of new blood cell production or hematopoisis. According to ayurveda, only due to healthy majja dhatu, rakta sara & Majja sara purusha exists. When majja dhatu is in healthy state, best quality of hematopoisis occurs & nourishment of shukra dhatu takes place. Mridwanga, balavanta, snigdha varna & gambhira swara, sthula-dirgha vritta sandhayah and maha netra are the benefits occurs in majja sara purusha. In this clinical study, total 30 patients having the complaints of bhrama and timira darshanam as mentioned by acharyas in majja kshaya, the main symptoms of a majjakshaya related with poor erythropoiesis were treated with Panchatikta Ghrita Guggulu. Results proved that Panchatikta Ghrita Guggulu provided significant relief in the disease majja kshaya w.s.r. to erythropoiesis.